Phosphoinositide 3-Kinase Promotes Oxidative Burst, Stomatal Closure and Plant Immunity in Bacterial Invasion - Zhang, Huiying; Liu, Xin; Zhang, Xiyong; Qin, Ningning; Xu, Kaifang; Yin, Weihua; Zheng, Yueqin; Song, Yuanyuan; Zeng, Rensen; Liu, Jian (Frontiers in Plant Science, 2020)
Phosphoinositide 3-kinase (PI3K) plays a vital role in plant response to abiotic stress. However, the role of PI3K in plant immunity is largely unknown. This study showed that PI3K enhanced Arabidopsis resistance to Pseudomonas syringae pv tomato DC3000 (Pst DC3000) and Pst DC3000 (avrRpt2). Overexpression of AtVPS34 promoted stomatal closure while PI3K inhibitors blocked that after spray inoculation. Additionally, gene expression of AtVPS34 was increased upon infection by Pst DC3000 (avrRpt2), and SA upregulated AtVPS34 gene expression in this process. Furthermore, overexpression of AtVPS34 enhanced PR gene expression after syringe infiltration with Pst DC3000 (avrRpt2), while PI3K inhibitors inhibited that. The production of hydrogen peroxide and the expression of gene encoding antioxidant enzyme were both enhanced in AtVPS34 overexpressing lines after spray inoculation or syringe infiltration with Pst DC3000 (avrRpt2). Collectively, these results unraveled a novel and broad role of PI3K in plant immunity which promoted stomatal closure and PR gene expression possibly via regulating ROS production.